Developmental evaluation applying complexity concepts to enhance innovation and use - Patton, Michael Quinn (New York Guilford Press, 2011)
Developmental evaluation (DE) offers a powerful approach to monitoring and supporting social innovations by working in partnership with program decision makers. In this book, eminent authority Michael Quinn Patton shows how to conduct evaluations within a DE framework. Patton draws on insights about complex dynamic systems, uncertainty, nonlinearity, and emergence. He illustrates how DE can be used for a range of purposes: ongoing program development, adapting effective principles of practice to local contexts, generating innovations and taking them to scale, and facilitating rapid response in crisis situations. Students and practicing evaluators will appreciate the book's extensive case examples and stories, cartoons, clear writing style, "closer look" sidebars, and summary tables. Provided is essential guidance for making evaluations useful, practical, and credible in support of social change.
Includes bibliographical references (p. 341-353) and indexes.
Keywords: Project management--Evaluation.